Nordic walking: a systematic review - Pedro Pérez-Soriano; Alberto Encarnación-Martínez; Inmaculada Aparicio-Aparicio; José Vicente Giménez; Salvador Llana-Belloch (Asociación Española de Ciencias del Deporte, 2014)
Nordic walking (NW) a new walking modality performed with poles as an aid to traction has been widely spread in recent years. Despite the many papers published many aspects are still unknown. So a systematic review has been done with the aim of presenting the state of the art and suggesting future research. Papers found were grouped in three categories: 31% were on body's physiological response, 45%, were on fitness programs aimed at improving people's health and 24% were on biomechanical aspects. It can be concluded conclude that NW can be considered an intermediate locomotive mode between walking and running. Oxygen consumption, heart rate, expiratory volume, energy expenditure and lactic acid levels are increased during NW at the same subjective speed as walking. There is no evidence of any contraindication in NW in the groups studied, and therefore it is an activity of great interest to most of the population. However, all is not yet elucidated and further research is needed.